MEMAHAMI KONSEP ISLAM REVISIONIS MUN’IM SIRRY - muhammad rafii (Nizham Jurnal Studi Keislaman, 2022)
The argument of this article is that the revisionist Islamic ideas and concepts popularized by Mun'im Sirry in Indonesia is an academic work that invites Islamic scholars to re-examine Islamic sources in order to find historical truth. For Mun'im Sirry Islam believed by Muslims has not been able to distinguish between historical facts and theological beliefs. The findings of this study are that Mun'im Sirry supports several theses of previous revisionist scholars such as John Wansbourgh and Ignaz Goldziher regarding the many historical distortions, teachings and rituals of Muslims which are actually different from early Islamic practice. However, Mun'im Sirry has his own unique revisionist concept of Islam. One of the factors causing this bias is because Muslims accept Islamic sources as taken for granted, that Islam is a religion that has been perfected. An important point for disseminating revisionist Islamic ideas is that new facts and interpretations are very important to support the construction of a tolerant, dialogical attitude in order to create a religious community that can live side by side and work together.